Pelatihan Pengoperasian Accurate Accounting di Industri 4.0 - Wailan' An, Evi Juita; Pandia, Sonya Enda Natasha S.; Sulia, Sulia; Riny, Riny; Loman, Devina (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The purpose of this activity is to enhance the competence and knowledge of students at SMA Swasta Wiyata Dharma and SMK Negeri 1 Medan. Through this program, it is expected that students’ skills in using accounting software, particularly Accurate version 5, will improve, from inputting financial transactions to generating financial reports. This community service activity is conducted over 3 days: January 24, 2024, April 1, 2024, and April 2, 2024. This activity successfully improved students' knowledge and skills in using Accurate accounting software. Based on the results of the pre-test and post-test, there was an increase in students’ understanding of Accurate usage at both SMK Negeri 1 Medan and SMA Swasta Wiyata Dharma Medan. The average post-test scores showed a significant increase compared to the pre-test, indicating an improvement in participants' competencies. Additionally, the awarding of prizes to active participants and those who could answer questions in the quiz demonstrated the students’ enthusiasm for participating in this activity